IMMUNOLOGICAL INDICATORS IN ACTINIC KERATOSIS - Аюбова Н.М. (Web of Journals Publishing, 2024)
The article discusses modern information on actinic keratosis, presents generalized data from scientific studies of immunological studies of the disease.
Keywords: actinic keratosis; solar keratosis; senile keratosis; precancerous skin lesion; squamous cell carcinoma in situ; solar irradiation; ultraviolet light; interleukini, IL-4, IL-10, TNF.